Calibration of modular reconfigurable robot systems - Chen, I-Ming. (2008)
This report describes both the theoretical and experimental aspects of robot kinematics calibration. The kinematics of the modular robot is established in a local coordinate description based on the Product-of-Exponentials formula, termed Local POE kinematics.